Analisis Peran Minat dan Bakat dalam Proses Pembelajaran: Studi Kasus pada Hasil Belajar Siswa SMA - Mahnil, Nisa; Fadieny, Nurul; Safriana, Safriana (Universitas Garut, 2024)
This study aims to analyze the role of interests and talents in the learning process of high school students and their impact on academic achievement. The method used is Systematic Literature Review (SLR), involving the selection and analysis of five articles relevant to the research topic. The results show that strong interest enhances students' intrinsic motivation, while natural talents help them understand and apply academic concepts more effectively. Additionally, metacognitive skills significantly contribute to learning outcomes, particularly in complex subjects such as chemical equilibrium. These findings emphasize the importance of learning approaches based on students' interests and talents, supported by student-centered teaching strategies. Inclusive education that accommodates the diversity of students' interests and talents is a crucial factor in creating an effective learning environment. Therefore, teachers and parents need to play an active role in motivating students to explore and develop their potential. This study recommends the development of innovative and sustainable learning strategies to improve student engagement and academic achievement. Further research is needed to examine other factors influencing the relationship between interests, talents, and learning outcomes.